The practice of female circumcision in Palopo city between religious and cultural teachings: A study of the Living Hadith Perspective - Langaji, Abbas; Ratnah Umar (Institut Agama Islam Negeri Palopo, 2023)
This study examines the practice of female circumcision in Palopo City from the perspective of living hadith, which integrates religious and cultural teachings in daily life. The practice of female circumcision, although controversial, is still practiced in Palopo as part of family and community traditions. This study uses the living hadith approach to understand how the people of Palopo interpret and apply the hadith related to female circumcision in their local context. The findings show that female circumcision is seen as a form of fulfilling religious teachings and maintaining the purity and honor of girls, while also being an important rite of passage in the local culture. However, with increasing awareness of health and human rights issues, there have been changes in views and practices among communities. This research provides insight into the complexity of the interaction between religious and cultural teachings in the practice of female circumcision in Palopo City, and the importance of a holistic and contextual approach in understanding and addressing this issue.